Религиоведение: словарь / [Аверченко И. В. и др. ] ; под ред. Е.С. Элбакян - Элбакян Екатерина Сергеевна (Gaudeamus, 2007)
Экземпляры: СЭ (20080414) / Инвентарный номер: 1069002 / Цена: / Сис.шифр: 86.2 / Авт.знак: Р 36 / ГРНТИ: 21 / ББК: 86.2